Stimulation of PBMC and Monocyte-Derived Macrophages via Toll-Like Receptor Activates Innate Immune Pathways in HIV-Infected Patients on Virally Suppressive Combination Antiretroviral Therapy - Merlini, Esther; Tincati, Camilla; Biasin, Mara; Saulle, Irma; Cazzaniga, Federico Angelo; d’Arminio Monforte, Antonella; Cappione, Amedeo J.; Snyder-Cappione, Jennifer; Clerici, Mario; Marchetti, Giulia Carla (Frontiers in Immunology, 2016)
In HIV-infected cART-treated patients, immune activation and microbial translocation persist and associate with inadequate CD4 recovery and morbidity/mortality. We analyzed whether alterations in the TLR pathway could be responsible for the immune hyper-activation seen in these patients. PBMC/MDM of 28 HIV+ untreated and 35 cART treated patients with HIV-RNA<40cp/mL (20 Full Responders: CD4≥350; 15 Immunological Non Responders:CD4<350) as well as of 16 healthy controls were stimulated with a panel of TLR agonists. We measured: CD4/CD8/CD14/CD38/HLA-DR/Ki67/AnnexV/CD69/TLR4/8 (Flow Cytometry); PBMC expression of 84 TLR pathway genes (qPCR); PBMC/MDM cytokine release (Multiplex); plasma LPS/sCD14 (LAL/ELISA). PBMC/MDM from cART patients responded weakly to LPS stimulation but released high amounts of pro-inflammatory cytokines. MDM from these patients were characterized by a reduced expression of HLA-DR+MDM and failed to expand activated HLA-DR+CD38+ T-lymphocytes. PBMC/MDM from cART patients responded more robustly to ssRNA stimulation; this resulted in a significant expansion of activated CD38+CD8 and the release of amounts of pro-inflammatory cytokines comparable to those seen in untreated viremic patients. Despite greater constitutive TLR pathway gene expression, PBMC from Immunological Non Responders seemed to up-regulate only type I IFN genes following TLR stimulation, whereas PBMC from Full Responders showed a broader response. Systemic exposure to microbial antigens drives immune activation during cART by triggering TLRs. Bacterial stimulation modifies MDM function/pro-inflammatory profile in cART patients without affecting T-lymphocytes; this suggests translocating bacteria as selective stimulus to chronic innate activation during cART. High constitutive TLR activation is seen in patients lacking CD4 recovery, suggesting an exhausted immune milieu, anergic to further antigen encounters.